2021
DOI: 10.1136/bmjdrc-2020-001858
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes in COVID-19 and diabetes: a retrospective cohort study from three London teaching hospitals

Abstract: IntroductionPatients with diabetes mellitus admitted to hospital with COVID-19 have poorer outcomes. However, the drivers of poorer outcomes are not fully elucidated. We performed detailed characterization of patients with COVID-19 to determine the clinical and biochemical factors that may be drivers of poorer outcomes.Research design and methodsThis is a retrospective cohort study of 889 consecutive inpatients diagnosed with COVID-19 between March 9 and April 22, 2020 in a large London National Health Service… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 32 publications
4
43
1
2
Order By: Relevance
“…A study in Korea reported neutrality for COVI-19 mortality (OR 0.84; 95% CI, 0.23–3.09) in SUs users vs. non-users [ 23 ]. A similar result was reported by Izzi-Engbeaya for deaths within 30 days (OR 0.66; 95% CI, 0.30–1.52) in univariate analysis [ 24 ] and by Silverii and colleagues [ 25 ]. The Coronavirus SARS-CoV-2 and Diabetes Outcomes (CORONADO) study also found a neutral effect of SUs/glinides on mortality (OR 0.83; 95% CI, 0.67–1.03) within 28 days [ 26 ].…”
Section: Sulphonylureassupporting
confidence: 86%
“…A study in Korea reported neutrality for COVI-19 mortality (OR 0.84; 95% CI, 0.23–3.09) in SUs users vs. non-users [ 23 ]. A similar result was reported by Izzi-Engbeaya for deaths within 30 days (OR 0.66; 95% CI, 0.30–1.52) in univariate analysis [ 24 ] and by Silverii and colleagues [ 25 ]. The Coronavirus SARS-CoV-2 and Diabetes Outcomes (CORONADO) study also found a neutral effect of SUs/glinides on mortality (OR 0.83; 95% CI, 0.67–1.03) within 28 days [ 26 ].…”
Section: Sulphonylureassupporting
confidence: 86%
“…Seven studies (13.5%) reported the unadjusted effect of frailty based on the CFS with delirium (OR 2.91; 95% CI 2.00–4.25; I 2 = 56%; Figure S6). 29,40,43,48,58,64,69 Eight studies (15.4%) reported an unadjusted association of frailty based on the CFS with ICU admission 8,23,28,29,39,40,43,69 (OR 0.24, 95% CI 0.08–0.71; I 2 = 92%; Figure S7), and three studies (5.8%) reported the adjusted association 8,67,69 (OR 0.87, 95% CI 0.56–1.35; I 2 = 69%; Figure S8). Six (11.5%) studies reported unadjusted associations between frailty based on the CFS and receipt of mechanical ventilation (OR 0.32, 95% CI 0.08–1.30; I 2 = 89%; Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…The details regarding excluded articles can be seen in Appendix A. As a result, 9 studies were included in this meta-analysis [21][22][23][24][25][26][27][28][29] with an overall of 19,660 Covid-19 patients with diabetes mellitus (Fig. 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%